Zoophytophagous mites can trigger plant‐genotype specific defensive responses affecting potential prey beyond predation: the case of Euseius stipulatus and Tetranychus urticae in citrus. Issue 7 (7th February 2019) - Cruz‐Miralles, Joaquín; Cabedo‐López, Marc; Pérez‐Hedo, Meritxell; Flors, Víctor; Jaques, Josep A
ABSTRACT: Background: Zoophytophagous predators can trigger plant defenses affecting prey populations beyond predation. Euseius stipulatus is a presumed zoophytophagous phytoseiid common in citrus. The response of citrus to one of its potential prey, Tetranychus urticae, is genotype dependent, with Citrus reshni and C. aurantium exhibiting extreme susceptibility and resistance, respectively. Volatile blends produced upon infestation affected the behavior of these two mites. We wondered whether E. stipulatus could trigger similar responses. Results: Euseius stipulatus triggered genotype‐dependent defense responses in citrus. Whereas C. aurantium upregulated the Jasmonic Acid, Salicylic Acid and flavonoids defensive pathways, C. reshni upregulated JA only. Likewise, different volatile blends were induced. These blends were exploited by E. stipulatus to select less‐defended plants (i.e., those in which higher pest densities are expected) and, interestingly, did not prevent T. urticae from choosing E. stipulatus ‐infested plants. To the best of our knowledge, this is the first time that this type of response has been described for a zoophytophagous phytoseiid. Conclusion: The observed responses could affect herbivore populations through plant‐mediated effects. Although further research is needed to fully characterize them and include other arthropods in the system, these results open opportunities for more sustainable and effective pest control methods (i.e., combining semiochemicals and biological control). © 2018 Society of Chemical Industry Abstract : Euseius stipulatus triggers genotype‐specific defensive responses in citrus, including the production of herbivore plant‐induced volatiles affecting conspecifics and potential prey beyond predation.